THE APPLICATION OF FORCE MAJEURE CLAUSES AS A BASIS FOR EMPLOYMENT TERMINATION IN INDONESIAN LABOR PRACTICES - Sani, Ayi Meidyna; Rasji, Rasji (EKSEKUSI, 2025)
The use of force majeure clauses as grounds for termination of employment (PHK) is increasingly common in employment practices, particularly in crisis situations that impact a company's operational capabilities. However, the use of force majeure as a reason for termination of employment often raises legal issues because it is often misinterpreted, over-extended, or used without meeting the normative requirements stipulated in the Manpower Law and its implementing regulations. This study aims to analyze the validity of using force majeure as a basis for termination of employment, identify its legal limitations, and examine the considerations of judges in several Industrial Relations Court and Supreme Court decisions related to this issue. The research method used is normative legal research with a statutory approach, a case approach, and a conceptual approach. The results indicate that force majeure can only be used as a basis for termination of employment if the event is beyond the company's control, unpredictable, and truly prevents the company from maintaining its employment relationship. Furthermore, judges tend to reject terminations based on force majeure if the company is still able to operate or if other alternatives exist, such as bipartite negotiations, rearranged working hours, or wage deferrals. Therefore, regulatory certainty and clarity are needed to prevent employers from misusing force majeure.Keywords: force majeure, Termination of Employment (PHK), Employment Law, Judge's Consideration